Does Religious Obedience Affect Happiness? The NU Muslims Indonesian Case - Anas Tania Januari; Muhammad Kholisul Imam (Journal of Islamic Civilization, 2023)
Happiness is one of the benchmarks of individual welfare. Currently, welfare is notonly calculated from the income but also the individual’s perspective on life. Welfareis a multi-dimensional component, and happiness is part of subjective well-being. Thisstudy aims to empirically prove the role of religious obedience on the happiness ofMuslims, especially for those closely related to Nahdlatul Ulama (NU). This researchapproach is quantitative with secondary data sources obtained from the 5th wave of theIndonesia Family Life Survey (IFLS). This study took 481 respondents which wereestimated by the logistic regression model. The results show that piety is empiricallyproven to increase the happiness of NU Muslims in Indonesia. In addition, economicfactors such as income also play a role in increasing happiness. Other result shows thatage is also determinant of happiness which display distinct functional relations (lineardecline and U-shape). While formal education in madrasa schools has no impact onhappiness. The contribution of this research is that NU institutions will focus more onactivities that can increase citizen piety.